1985
DOI: 10.1071/ph850337
|View full text |Cite
|
Sign up to set email alerts
|

A Neutron Spectrometer with a Two-dimensional Detector for Time-resolved Studies

Abstract: Aust. J. Phys., 1985, 38, 337-51 An intermediate resolution neutron spectrometer for collecting diffraction data with the range Q = 0·01-3·0 A has been built for analysing the structural organization of membranes, polymers and other molecular aggregates. This spectrometer has a position-sensitive detector with a capability for time-resolved data collection which may be used to study conformational changes in dynamical systems. A double multilayer monochromator assembly is used to monochromate neutrons. Oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…And, perhaps more important, the requirement of large single crystals (with volumes in the range of 1-10 mm 3 ) has been a serious limitation. Breakthrough technical events in the neutron macromolecular field have been the development of the neutron imaging plate (NIP) [3][4][5], the adoption of Laue methods at reactor sources [6] and most recently the LANSCE time-of-flight electronic detector for neutron protein crystallography [8,9]. Thus these three technical developments have allowed exploration of the main frontiers of the capability of neutron protein crystallography: namely, the time needed to measure data, the diffraction resolution reached and the molecular weight ceiling reachable.…”
Section: Introductionmentioning
confidence: 99%
“…And, perhaps more important, the requirement of large single crystals (with volumes in the range of 1-10 mm 3 ) has been a serious limitation. Breakthrough technical events in the neutron macromolecular field have been the development of the neutron imaging plate (NIP) [3][4][5], the adoption of Laue methods at reactor sources [6] and most recently the LANSCE time-of-flight electronic detector for neutron protein crystallography [8,9]. Thus these three technical developments have allowed exploration of the main frontiers of the capability of neutron protein crystallography: namely, the time needed to measure data, the diffraction resolution reached and the molecular weight ceiling reachable.…”
Section: Introductionmentioning
confidence: 99%
“…Delaying the signals of the cathode wires and measuring the time difference of these signals, the position of the event recording wires in the two cathode planes with orthogonal wire directions can be identified and thus the position of the event in the detector plane determined [1][2][3][4]. Recording the time and knowing the length of flight (chopper-to-detector distance), the velocity (energy, wavelength) of the absorbed neutron can be computed [5]. The ratio between the number of detected neutrons and the number of neutrons that reach the detector gas chamber is the detection efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The development of position-sensitive area detectors (Fischer, Radeka & Boie, 1983) for neutrons (Boie et al, 1982) and X-rays (Hamlin, 1982(Hamlin, , 1988 demonstrated the need for fast data-acquisition systems (Schoenborn, Saxena, Stamm, Dimmler & Radeka, 1985) to interface with modern fast computers. Such devices should be front ends to commercial systems, use as many commercial components as possible and be more or less machine independent.…”
Section: Introductionmentioning
confidence: 99%